Cervical esophageal rupture after blunt trauma resulting from a car accident - Misiak, Piotr; Jabłoński, Sławomir; Terlecki, Artur (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Traumatic perforation of the cervical esophagus due to blunt trauma is a very rare condition which continues to be associated with significant mortality rates. The symptoms and signs of this injury are often masked by or ascribed to more common blunt thoracic injuries. This paper presents a case of cervical esophageal perforation secondary to blunt trauma resulting from a car accident. The injury was diagnosed early by computed tomography examination, and the patient underwent prompt and successful surgical repair performed to prevent the development of descending mediastinitis.